(untitled) - Dampier, William Cecil (Cambridge [Eng.], 1948)
This famous book, first published in 1929 was considerably revised and enlarged in its fourth edition, which is being reprinted now. This edition had the addition of a postscript by Professor I. Bernard Cohen containing a list of reading, with comments on them to guide the readers.
Keywords: Science,Philosophy,Khoa học,Triết học; History,Lịch sử